ASSESSMENT OF RISK MANAGEMENT PRACTICES AND THEIR IMPACT ON THE QUALITY OF SERVICES IN PALESTINIAN MUNICIPALITIES, MODERATED BY ORGANIZATIONAL CULTURE - Assoud, Somaya (An-Najah National University, 2025)
Municipalities are critical in the provision of necessary public services in the local governance context, but due to operational limits, organizational resources, and political instabilities, their performance is likely to be affected. This study aims to investigate how Risk Management Practices (RMP) can influence Quality of Services (QoS) among Palestinian municipalities and assess the effect of Organizational Culture (OC) as a mediator. A quantitative study design was used, and a self-administered questionnaire was deployed to senior municipal officials throughout the West Bank. SmartPLS was used to examine 135 valid responses in order to test the hypotheses of the structural model proposed and the hypotheses of the study itself. The findings indicate that the level of service quality is high, but the practices of both RMP and OC are moderate. Also, the findings indicate that RMP does not substantially influence the level of the QoS; however, it produces a positive and significant indirect impact on the latter via OC, which is an example of its mediating effect. It implies that the success of efforts toward risk management in terms of delivering positive service results is highly dependent on the robustness of organizational culture in the municipalities, namely, coherent work practices, norms shared, and supportive leadership. Organizational culture is highlighted as a critical component in promoting service quality in the event of a conflict and resource shortage, thus adding to the theoretical debates on risk management in the area of the public sector. The implications of the findings can be applied in practice by policy-makers and local authorities, who need to enhance an organizational culture of effective risk management that would result in more stable, uniform, and responsive services. Keywords: Risk management practices (RMP), organizational culture (OC), quality of services (QoS), public sector, Palestinian municipalities
التقييم لممارسات إدارة المخاطر وتأثيرها على جودة الخدمات في البلديات الفلسطينية، الثقافة التنظيمية كمتغير وسيط